Development-Dependent Plasticity in Vasoactive Intestinal Polypeptide Neurons in the Infralimbic Cortex - Collins, Stuart A (Cereb Cortex Commun, 2021)
The onset of several neuropsychiatric disorders including anxiety disorders coincides with adolescence. Consistently, threat extinction, which plays a key role in the regulation of anxiety-related behaviors, is diminished during adolescence. Furthermore, this attenuated threat extinction during adolescence is associated with an altered synaptic plasticity in the infralimbic medial prefrontal cortex (IL-mPFC), a brain region critical for threat extinction. However, the mechanism underlying the altered plasticity in the IL-mPFC during adolescence is unclear. Given the purported role of vasoactive intestinal polypeptide expressing interneurons (VIPINs) in disinhibition and hence their potential to affect cortical plasticity, we examined whether VIPINs exhibit an adolescence-specific plasticity in the IL-mPFC. We observed an increase in GABAergic transmission and a decrease in excitability in VIPINs during adolescence. Male mice show a significantly higher VIPIN-pyramidal neuron GABAergic transmission compared with female mice. The observed increase in GABAergic transmission and a decrease in membrane excitability in VIPINs during adolescence could play a role in the altered plasticity in the adolescent IL-mPFC. Furthermore, the suppression of VIPIN-mediated GABAergic transmission in females might be relevant to sex differences in anxiety disorders.